Laparoscopic Cholecystectomy; Conversion Rate, Experience of a Single Surgeon over 4-year period - Ali Javaid; Tahir Bashir; Maratab Ali (Journal of Surgery and Surgical Research - Peertechz Publications, 2017)
To evaluate the conversion rate of lap cholecystectomy and analyze the factors leading to the conversion to open surgery. Design: Observational Study Place and Duration: Department of surgery, Doctor's Hospital and Azra Naheed Medical College Lahore, Pakistan Patients and Methods: We retrospectively analysed 250 patients admitted with gallstone disease who were deemed to be fit for laparoscopic procedure. (June 2011 through May 2016) Results: The conversion rate in our study was 2.4%. We found it to be significantly lower than the majority of studies. The conversion was mainly due to dense adhesions in Calot's triangle, previous multiple surgeries, a case of cholecystoduodenal fistula and Mirizzi's syndrome. The rate of conversion is higher in male patients and in acute cases. Conclusion: The conversion rate is 2.4% in all the laparoscopic cholecystectomies. Male patients and acute case has a higher probability of conversion. High volume surgeon (>100 cases) as in our study has lower than normal conversion rate.